Moral capital : foundations of British abolitionism - Brown, Christopher Leslie (Published for the Omohundro Institute of Early American History and Culture, Williamsburg, Virginia., 2006)
"Revisiting the origins of the British antislavery movement of the late eighteenth century, Christopher Leslie Brown challenges prevailing scholarly arguments that locate the roots of abolitionism in economic determinism or bourgeois humanitarianism. Brown instead connects the shift from sentiment to action to changing views of empire and nation in Britain, particularly the anxieties and dislocations spurred by the American Revolution"--Page 4 of cover.